Peripheral venous catheter related complications are common among paediatric and neonatal patients. (11th March 2015) - Unbeck, M; Förberg, U; Ygge, B‐M; Ehrenberg, A; Petzold, M; Johansson, E
Abstract Aim The aims of this study were to describe the characteristics of peripheral venous catheters (PVCs), including dwell time and reasons for removal, and explore predictors for PVC‐related complications. Methods We included PVCs in 2032 children – 484 neonatal and 1548 paediatric – from 12 inpatient units. Data were retrieved from the patient record system, and predictors for complications were explored using logistic regression analyses. Results Just over one‐third (35.4%) of the PVCs were removed due to complications, in particular infiltration and occlusion (51.9 and 48.4/1000 PVC days, respectively). PVC survival time was shorter in neonatal than paediatric patients (4 versus 5 days), and infiltration was more frequent in neonatal patients (92.8 versus 38.7/1000 PVC days). Infiltration was associated with younger age (odds ratio 0.97) for neonatal patients and with younger age (OR 0.96), insertion in the bend of the arm (OR 1.48) or ankle (OR 2.81) for paediatric patients. Occlusion was, both for neonatal and paediatric patients, associated with longer dwell time (OR 1.32 and 1.22 respectively), insertion in the ankle (OR 5.00 and 3.51) or foot (OR 3.47 and 1.99). Conclusion PVC‐related complications, particularly infiltration and occlusion, were more common in hospitalised children but decreased with the child's age.